Crystal structure of ivermectin hemihydrate ethanolate, (C48H74O14)(H2O)0.5(C2H5OH)0.82. Issue 4 (December 2021) - Kaduk, James A.; Tanis, Allison; Tovar, Alyssa; Boaz, Nicholas C.; Gindhart, Amy M.; Blanton, Thomas N.
Abstract : The crystal structure of ivermectin hemihydrate ethanolate has been solved and refined using synchrotron X-ray powder diffraction data and optimized using density functional techniques. Ivermectin hemihydrate ethanolate crystallizes in space group C2 (#5) with a = 40.9374(10), b = 9.26951(6), c = 14.9488(2) Å, β = 73.047(1)°, V = 5426.12(8) Å 3, and Z = 4. The structure consists of layers of ivermectin molecules parallel to the bc -plane. The water and ethanol molecules reside in small voids in the structure. The water molecule, the ethanol molecule, and hydroxyl groups act as donors in O–H⋯O hydrogen bonds. Several C–H⋯O hydrogen bonds were detected. The powder pattern has been submitted to ICDD for inclusion in the Powder Diffraction File™.